Meeting Of The Board Of Directors, Jan. 24, 1919 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
At the meeting of the Board of Directors the following resolution was passed: "The members of the Board of Directors of the American Institute of Mining Engineers desire: to place on record their appreciation of the very great generosity of one of their colleagues and a member of the Board, George D. Barron, expressed in his gift of $5000 to relieve the financial stringency caused by the unusual expenditures of the Institute for war work and the remission of dues of those members on active service." By-Law VIII. was amended to make a slight change in District No. 5. The report of the Auditing Committee was accepted. Tellers were appointed to: count the ballots on officers and on the proposed amendment. The proposed budget for the year 1919 was presented. The following resolution re Secretary Emeritus Rossiter W. Raymond, which had been prepared, by request, by Dr. A. R. Ledoux was then unanimously adopted. "The Board of Directors of the American Institute of Mining Engineers would place upon its minutes its profound sense of loss and sorrow in the death of Rossiter Worthington Raymond, Ph. D., LL. D., Secretary Emeritus of the Institute. Both as one of its founders and as its Sec-retary for 27 years, his was the guiding spirit of the Institute for more than a generation. "During the greater part of this long period, it might almost have been said that the Institute was Dr. Raymond-and Dr. Raymond the Institute. When with the progress of growth and development, great changes were introduced, Dr. Raymond acquiesced in these in spite of some misgivings, such as those with which a father might contemplate the emergence of his child from the careful supervision of the home; but as Secretary Emeritus for the past eight years, lie was always ready with valuable advice and helpful suggestion.